View Single Post
Old 2020-11-11, 15:26   #6
Alberico Lepore
 
Alberico Lepore's Avatar
 
May 2017
ITALY

3·7·23 Posts
Default

another type of implementation based on the same principle
is this [if I have not made mistakes]



3*(((2*190-3*y+1)/24)+3*x*(x+1)/2)+1=A
,
y=2*[(-1)^((y+1)/2-1)]*a+(-1)^[(-1)^((y+1)/2)]
,
3*(((2*A-3*a+1)/24)+3*x*(x+1)/2)+1=B
,
[(-1)^((y+1)/2-1)]*a=2*[(-1)^[[[(-1)^((y+1)/2-1)]*a+1]/2-1]]*b+(-1)^[(-1)^[[[(-1)^((y+1)/2-1)]*a+1]/2]]
,
3*(((2*B-3*b+1)/24)+3*x*(x+1)/2)+1=C
,
[(-1)^[[[(-1)^((y+1)/2-1)]*a+1]/2-1]]*b=2*[(-1)^[[[(-1)^[[[(-1)^((y+1)/2-1)]*a+1]/2-1]]*b+1]/2-1]]*c+(-1)^[(-1)^[[[(-1)^[[[(-1)^((y+1)/2-1)]*a+1]/2-1]]*b+1]/2]]
,
3*(((2*C-3*c+1)/24)+3*x*(x+1)/2)+1=C
,
c=1



which of the two is better in your opinion?



UPDATE:

There are some mistakes
tomorrow I will try to update

Last fiddled with by Alberico Lepore on 2020-11-11 at 17:16 Reason: UPDATE
Alberico Lepore is offline   Reply With Quote